2012
DOI: 10.4103/2278-9626.105381
|View full text |Cite
|
Sign up to set email alerts
|

Color differences between maxillar and mandibular incisors

Abstract: Context: Color difference between maxillar and mandibular incisors is an anticipated subject, and it will help dentists during color matching. Aim: The aim of this study was to evaluate color differences of the maxillar and mandibular incisors and to find out relationships between gender and age. Materials and Methods: This study was conducted on 125 participants (51 males and 74 females) between 16-63 age groups and totally over maxillar and mandibular 480 hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 17 publications
1
18
0
5
Order By: Relevance
“…The results of this study show a higher value of color for central incisors compared to lateral incisors and canines. Canines were darker than lateral incisors which in turn, were darker than central incisors, which is in agreement with other studies [24].…”
Section: Discussionsupporting
confidence: 82%
“…The results of this study show a higher value of color for central incisors compared to lateral incisors and canines. Canines were darker than lateral incisors which in turn, were darker than central incisors, which is in agreement with other studies [24].…”
Section: Discussionsupporting
confidence: 82%
“…Many studies have been conducted on the measurement and distribution of tooth color, and researchers have used both conventional and digital methods in their tooth color determinations . Digital devices can provide a standard measurement of the tooth and are more reliable . Previous studies comparing conventional and digital tooth color measurement methods have reported that digital devices provided better results .…”
Section: Discussionmentioning
confidence: 99%
“…Ensuring the natural tooth form and color is important for the esthetic success of a restoration . The anterior region is one of the most striking areas for a dental restoration; therefore, tooth color determination is very important for esthetic dentistry.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dudak, yüz ve birbiri ile uyum içinde dizilmiş, uygun renk, form, yüzey özellikle-rine sahip dişler kişinin iletişim becerisini ve kendine olan güvenini arttırır. [1][2][3] Diş hekimliğindeki gelişmelerle estetik ön plana çıkmış ve renk, en az form ve fonksiyon kadar önemli hale gelmiştir. Seçilen rengin doğal diş-lerle uyumlu olması hasta memnuniyetini arttırır ve restorasyon değişimi ile oluşacak ekstra maliyetlerin önüne geçer.…”
Section: Introductionunclassified